IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL), SOMATIS AUDITORI VISUAL INTELEKTUAL (SAVI), DAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA KETERAMPILAN MEMBACA MEMAHAMI ISI CERITA SISWA DI KELAS 4 SDN GUNUNG MELATI 2 DI KAB - Ainun Azzahra; Mahmuddin (STKIP Subang, 2026)
ABSTRACT Fourth-grade students in Indonesia face low learning outcomes, particularly in reading and story comprehension. Students' reluctance to actively participate in class, their lack of assurance of understanding the material, and a lack of variety in teaching strategies are some contributing factors. By applying PBL, SAVI, and CIRC theories, the purpose of this study was to characterize teacher activities and analyze student activities and learning outcomes. This study used the CAR method. The study was conducted in two cycles, with two meetings in each cycle. The participants were fourth-grade students of SDN Gunung Melati 2. Data were collected through tests and observations, and analyzed qualitatively in several stages, such as data reduction, presentation of findings, drawing conclusions, and verification. Furthermore, the development of student learning success was assessed using quantitative analysis, both in written and oral exams. Instructor activity received a score of 18 in the first cycle, which is classified as